School ethos and the association to upper secondary school students’ school engagement: A multilevel study - Joacim Ramberg (Education in the North, 2019)
Students’ school engagement has an intrinsic democratic value and is positively associated to a range of student outcomes. It is also established in international and national policy guidelines that students have the right to participate in decision-making concerning their education. Previous research shows that students’ school engagement is influenced by a variety of factors at different structural levels, but few comprehensive studies have assessed the relation to school-contextual factors, such as school ethos, while also taking student-level sociodemographic characteristics into account. Therefore, this study aims to examine the associations between teacher-rated school ethos and three dimensions of students’ school engagement: a) participation in educational planning; b) involvement in decisionmaking of important issues; and c) students’ opportunities for influence. Data were collected with two separate surveys among 5,168 students and 1,204 teachers across 58 upper secondary schools in Stockholm, and subsequently linked together. Due to the hierarchical nature of the data, multilevel modelling was applied. Two-level linear regression analyses showed that schools with a strong school ethos were associated with higher ratings of the three dimensions of students´ school engagement. Results indicate that a strong and vital school ethos has the potential to raise the levels of students’ school engagement.